The Role of Pragmatics in Intercultural Communication Competence - Ananda Sasi Kirana; Aidil Syah Putra; Maely Aisyah Rezqy Lubis; Sintiya Ridiyanti (Universitas Batanghari Jambi, 2026)
In the context of globalization, interaction among individuals from different cultural backgrounds has become increasingly common in social, educational, and professional domains. Intercultural communication competence (ICC) is understood as the ability to communicate effectively and appropriately in such interactions, which involves not only linguistic proficiency but also pragmatic awareness. This study seeks to investigate the role of pragmatics in intercultural communication competence by examining participants’ perceptions of pragmatic use in intercultural communication. Using a descriptive qualitative research design, the study involved 15 seventh-semester students from the English Education Study Program at Universitas Muhammadiyah Tangerang. Data were gathered through closed-ended written interview questions distributed online via Google Forms. The data were analyzed qualitatively by interpreting response patterns related to pragmatic competence. The findings reveal that participants largely acknowledge the significance of pragmatic awareness, particularly in relation to politeness strategies, understanding implied meanings, and sensitivity to cultural norms, in achieving effective intercultural communication. Furthermore, the results indicate that grammatical accuracy alone does not ensure communicative success across cultures, as pragmatic competence plays a vital role in reducing misunderstanding and promoting appropriate interaction. This study concludes that pragmatics is a fundamental component of intercultural communication competence and emphasizes the need to integrate pragmatic awareness into language education to enhance intercultural communicative effectiveness.